Pengembangan Pariwisata Kota Taman Bungkul Sebagai Tujuan Wisata Di Kota Surabaya - Agres Tjahjoko (HOSPITALITI DAN PARIWISATA, 2018)
Surabaya tourism is one activity that is attractive to domestic and International Tourist, they manage their routinity and boredom by visiting a place where they can find comfort and pleasure. Tourism attraction is very important to attract tourist visit, one of the tourism object visited the most is taman bungkul Surabaya. Great location in the middle of the city, with an area of 900 m2 and is easily accessed. Taman bungkul has a complete facilities, the are childrens playground, jogging track, 33 m diameter amphitheatre, comfortable seat and unique, free wifi conection, those are all provided freely to satisfy visitors. All of those are making taman bungkul crowded with visitors. Visitors are from cycling community, motorcycle communit,pedestrians, etc. They come to meet their friends and relax with them. Problems emerge in Saturday and Sunday, parking capacity is not sufficient an it jeopardize the traffic flow. Toilet also not adequate because it is available only on a spot. Methods used to obtain primary data is direct field observation, interview with visitors and some small business owners, and documentation by photo taking. Secondary data is obtained by studying books related to this research topic. A finding resulted from this research: taman bungkul Surabaya has the potency to become the iconic of Surabaya as a place for tourists to visit, by managing better the parking area, the stree vendors and the toilet.